Smart Packaging for Chicken Meat Quality: Absorbent Food Pad and Whatman Paper Applications - Dirpan, Andi; Iqbal, Muhammad; Yumeina, Diyah; Prahesti, Kusumandari Indah; Djalal, Muspirah; Syarifuddin, Adiansyah; Bahmid, Nur Alim; Bastian, Februadi; Salengke, Salengke; Suryono, Suryono (Indonesian Food Science and Technology Journal, 2023)
Quality and shelf-life extension are major concerns in the development of meat packaging systems. The purpose of this study was to determine the effectiveness of absorbent food pads combined with intelligent packaging as well as to determine the correlation between active packaging and smart indicator labels. The active packaging applied absorbent food pads as carriers of active ingredients from basil and lemongrass, which are expected to extend the shelf life of chicken meat and maintain its quality. Meanwhile, intelligent packaging employs Whatman paper treated with Phenol Red (PR), providing real-time information on the quality of chicken meat. Various chicken meat spoilage test parameters such as thiobarbituric acid (TBA), total volatile base nitrogen (TVBN), total bacteria of total plate Count (TPC), and pH were tested at chiller temperature (4oC) every 3 Ã— 24 hours. The results of this study indicated that absorbent food pad with lemongrass essential oil can extend the shelf life of chicken meat by 3 days while, the intelligent indication labelâ€™s color profile changed from yellow at the beginning of application to red during chicken spoilage. Therefore, smart packaging from a combination of an absorbent food pad as active packaging and phenol red indicator label as intelligent packaging can potentially extend the shelf life of chicken and monitor the condition of chicken meat during storage.